Surgery for allergic rhinitis. Issue 2 (September 2014) - Chhabra, Nipun; Houser, Steven M.
<x xml:space="preserve">Abstract</x> Background Allergic rhinitis (AR) is a highly prevalent disorder that significantly impacts quality of life and affects millions of people annually. The most bothersome complaint is nasal obstruction, which is most commonly due to inferior turbinate hypertrophy. Methods This work presents a review of the literature and an overview of operative techniques. Results A variety of methods are available for addressing inferior turbinate hypertrophy in patients afflicted with AR. Although no single modality has been defined as the gold standard for treatment, the otolaryngologist should be familiar with an armamentarium of surgical techniques. Conclusion The inferior turbinate is the initial deposit point for allergens and undergoes dynamic changes through the allergic cascade, which results in nasal obstruction. Targeting the inferior turbinate to augment the nasal airway is the mainstay of surgical treatment in AR. Judicious technique and a mucosal sparing philosophy are necessary to maximize outcomes and improve quality of life.